DEVELOPMENT OF AN INSTRUMENT FOR THE EFFECTIVENESS OF RELIGIOUS CHARACTER EDUCATION PROGRAMS IN OVERCOMING STUDENT MORAL DEGRADATION - Sujanah, Nanah; Maisaroh, Ima; Ngulwiyah, Istinganatul (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to develop an instrument to assess the effectiveness of a religious character education program in addressing the moral degradation of students. The research employs a development model (research and design) based on primary data collected through a questionnaire consisting of 20 statements aligned with 10 indicators of character education. These indicators include understanding religious values, internalization of values, honesty, responsibility, tolerance, consistency in religious attitudes, social care, discipline in spiritual relationships, and satisfaction with the program. The research instrument uses a rating scale ranging from 1 to 5 and is validated by three education experts from the Faculty of Teacher Training and Education (FKIP). The sample consists of 25 first-semester students from the 2024-2025 academic year, class 1A of the Agribusiness Department, Faculty of Agriculture, Untirta. Data analysis includes content validity testing using Aiken’s V formula and intraclass correlation coefficients (ICC) for reliability testing. Empirical validity testing employs product moment analysis, and reliability testing uses Cronbach's alpha, analyzed using SPSS version 23. The findings reveal that: (1) Based on the content validity test, out of 20 statement items, 16 items demonstrate very high validity, and 4 items show 2 high validity, with an average content validity score of 1.000, interpreted as very high. The reliability test using intraclass correlation coefficients (ICC) yields an average measure of 0.971, indicating excellent instrument reliability. (2) From the empirical test results, out of 20 items, 19 items are valid, and 1 item is invalid, with a Cronbach's alpha value of 0.853 (>0.7), confirming the instrument's reliability. Therefore, the validated questionnaire consisting of 20 items is deemed suitable for measuring the effectiveness of the religious character education program